Education for Sustaining Peace through Historical Memory - Lis-Gutiérrez, Jenny Paola (Revista Complutense de Educación, 2022)
Corresponde a la reseña del siguiente libro "Education for Sustaining Peace through Historical Memory" Autor: Markus Schultze-Kraft Editorial: Palgrave Macmillan Año de publicación: 2022 Número de páginas: 119 ISBN: 978-3-030-93653-2 ISBNe: 978-3-030-93654-9